Il telerilevamento a supporto dell'Augmented Reality - Gemma, Filippo (GEOmedia, 2011)
Fondere insieme realtà e oggetti virtuali per muoversi al meglio con efficacia ed efficienza è quanto si propone, tramite la Realtà Aumentata, la AGI, Analytical Graphics Inc. di Exton (USA), distribuita in esclusiva in Italia da GMSPAZIO che offre il sistema STK, storicamente conosciuto come Satellite ToolKit che offre più di quarantamila utenti nel mondo un esteso set di funzionalità capaci di soddisfare ogni tipo di esigenza. Remote Sensing and Augmented Reality Augmented reality has been used for years in the broadcast industry. You see it every time the National Football League paints a yellow first-down line on the playing field. While it is com-monplace and easy to execute in con-trolled environments with fixed cam-era positions, predetermined angles and known terrain, the opposite is true in uncontrolled environments, such as battlefields in Kandahar. Nonetheless, augmented reality is essential for the warfighter, and the global intelligence community (IC) is faced with the chal-lenge of efficiently creating and dis-seminating intelligence products from increasing amounts of video data. AGI's Insight3D development library is helping to overcome many hurdles of ISR-focused augmented reality.